Morphing into the flock: a phenomenological study of native students immersed in the online learning platforms (Conference on English Language Teaching, 2023)
Utilization of online resources among native language learners have been studied, putting emphasis on the various experiences of this minority group in the academe. Thus, the phenomenological study aimed to explore the emerging issue with three objectives set: positive and negative experiences, challenges faced, and coping strategies developed. Data were gathered using in-depth interview while the data analysis made use of thematic patterning.  Outcomes unveiled mixed experiences of native learners, with fewer positive and more negative trends. The study also revealed native students' unreadiness for online learning utilization. Finally, the result conveyed the streamlined blending strategies of native students to cope with online learning. These findings were pivotal to future development UMDC's educational policy, particularly in utilizing online learning modalities, and enrichment to the University's native groups of students. This research is substantial in revitalizing the learning experiences of native students, teaching considerations, and igniting the engagement of the stakeholders as a whole.